Hepatoprotective and Anti-Oxidative Effects of Total Flavonoids From Qu Zhi Qiao (Fruit of Citrus Paradisi cv.Changshanhuyou) on Nonalcoholic Steatohepatitis In Vivo and In Vitro Through Nrf2-ARE Signaling Pathway - Shi, Zheng; Li, Ting; Liu, Yuwen; Cai, Tiantian; Yao, Wendong; Jiang, Jianping; He, Yinghua; Shan, Letian (Frontiers in Pharmacology, 2020)
Nonalcoholic steatohepatitis (NASH) is a liver disease defined as the dynamic condition of hepatocellular injury during the progress of nonalcoholic fatty liver disease (NAFLD). Total flavonoids from the dry and aged fruits of Citrus aurantium ‘Changshan-huyou’ (Qu Zhi Qiao, QZQ) are purified and named TFCH. This study was purposed to investigate and analyze the effect of TFCH on NASH model through Nuclear factor erythroid 2-related factor 2 (Nrf2)- antioxidant response elements pathway in vivo and vitro. In vivo study was performed using male C57BL/6 mice fed with high fat diet 16 weeks for NASH model. After 7-week modeling, mice in TFCH-treated group were daily treated with intragastric administration of TFCH at 25 mg/kg, 50 mg/kg, 200 mg/kg respectively for successive 8 weeks. Histopathological and immunohistochemical analyses were conducted for evaluating severity of NASH-mice model and the effect of TFCH treatment. In vitro experiment was performed by using human LX-2 cells and cultured with Free fatty acid (FFA) (Oleic acid: palmitic: l: 0.5 mmol/L) for 24h and then treated with TFCH at different concentrations (0, 25, 50, 100, 200 mg/ml) for 6h,12h and 24 h. Anti-apoptosis effect of TFCH on LX-2 cells cultured with FFA was revealed by the CCK-8 assay. Lipid parameters and oxidative stress markers were measured in vivo and in vitro, results showed that TFCH dose-dependently and greatly increased the antioxidant ability and reduced the oxidative damage in NASH model. The protein expression of Nrf2 and the downstream target genes in mice liver and human LX-2 cells were tested by Western blot analysis to investigate the possible molecular mechanisms of TFCH. Our results indicated that TFCH up-regulated protein expression of these genes and have the significant influence in activating the Nrf2-ARE signaling pathway. This study shows Nrf2-ARE signaling pathway may provide novel therapeutic opportunities for NASH therapy in the future.